Chad SME Competitiveness and Global Value Chain Upgrading Diagnostics with Focus on Opportunities in the Domestic and Regional Markets - World Bank (World Bank, Washington, DC, 2021)
This study aims to explore ways in which key competencies of the oil and gas industry could be leveraged to support the diversification of the Chadian economy. The analysis focused on identifying opportunities and prioritizing core competencies in specific segments of the oil and gas value chain where economic activities have the potential to grow and increase cross pollination, which can be achieved through policy reforms or the provision of public and private inputs.